PERANCANGAN WEB DESIGN SUBSTANCE BOARDRIDING STORE PADANG - ZAHRIAN ABDI, Nasbahri Couto, M.Sn., Dr. yahya, M.Pd. (DEKAVE : Jurnal Desain Komunikasi Visual, 2015)
Substance Boardriding store a surf or skate shop there a Padang city. Originated from some fellow surfing in Parkit Padang beach. Aroud a1999 this name Maniak Boardrider that giving idea to open a Surf Shop. Because began hectic a surfer foreign thet come to Mentawai for traveled surfing, but his little facility avaiable at the time.Finaly realized the idea to open a store in september 2001 untilizing the former movie theater lobby in picturesque into a small shop the name Substance which initialy only sell some clothing only from Quiksilver, Volcom and West SurfingProducts. All this time Substance Boardriding store only promotion through a facebook and twitter.Of it then make the design promotion Substance Boardriding store through media web design.Media web design is very good promotion in this business, Ass seen from the habits of the people are now dependent on cyberspace.Design method in use is analysis 5W+1H. Advantage of web media design, Design in this promotion faster conveyed and also more clear by looking at the components in web design. web design also more colorful and interristing to see making it more attractive market or consumers.The era of tecnology and information is now easily encountered paswoowod use, so it can be useed for promotional Substance Boardriding store in the form of web design. Suported by orther media, Namely poster, sticker, pin, name card, tote bag, hat, handbook, key chain, mug, and T shirt.Keyword : Design, web design, Substance Boardriding store